2018
DOI: 10.1007/s40263-018-0575-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Opicinumab in Acute Optic Neuritis Using Multifocal Visual Evoked Potential

Abstract: BackgroundMultifocal visual evoked potential (MF-VEP) assesses a wider visual field than full-field VEP (FF-VEP) and potentially offers a more precise analysis of optic nerve injury and repair following optic neuritis. MF-VEP may offer advantages over FF-VEP as an endpoint in clinical trials of remyelinating therapies.ObjectiveMF-VEP testing was used to study changes in visual pathways in 48% of RENEW [phase II, opicinumab (anti-LINGO-1; BIIB033) vs. placebo after first acute unilateral optic neuritis] partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…In a substudy of a recent clinical trial assessing the monoclonal anti-LINGO-1 antibody opicinumab in acute ON, fellow eyes of placebotreated, but not opicinumab-treated, patients showed progressive multifocal visual evoked potential (VEP) amplitude loss over 8 months. 34 Similarly, Raz et al 16 found changes to the latency of late peaks of the VEP of NON eyes, which were not attributable to demyelination; the authors attributed these changes to an adaptive mechanism to maximize preservation of stereopsis in their patients with unilateral ON. We are unable to reach firm conclusions as to the etiology of our INL thickness changes, but we suggest subclinical inflammation of the fellow eye as a potential candidate.…”
Section: Discussionmentioning
confidence: 96%
“…In a substudy of a recent clinical trial assessing the monoclonal anti-LINGO-1 antibody opicinumab in acute ON, fellow eyes of placebotreated, but not opicinumab-treated, patients showed progressive multifocal visual evoked potential (VEP) amplitude loss over 8 months. 34 Similarly, Raz et al 16 found changes to the latency of late peaks of the VEP of NON eyes, which were not attributable to demyelination; the authors attributed these changes to an adaptive mechanism to maximize preservation of stereopsis in their patients with unilateral ON. We are unable to reach firm conclusions as to the etiology of our INL thickness changes, but we suggest subclinical inflammation of the fellow eye as a potential candidate.…”
Section: Discussionmentioning
confidence: 96%
“…Although slightly more time consuming, the latency results of mfVEP are more meaningful and reliable, which results in significantly smaller sample size needed to demonstrate remyelination. 37 Although we did not perform mfVEP in control subjects (which may be considered as another limitation), the conclusions were mainly drawn from intrasubject analysis between ON and NON in patients with MS.…”
Section: Discussionmentioning
confidence: 98%
“…The study showed a trend toward improvement in the affected eye and significant improvement in the fellow eye. 22 However, there is a lack of qualified methods to directly assess CNS remyelination in humans.…”
Section: Discussionmentioning
confidence: 99%
“…12,20 It is currently being investigated in clinical trials as a potential treatment to repair neuronal damage that occurs in the CNS of individuals with multiple sclerosis (MS) (AFFINITY: clinical trial.gov number NCT03222973). 3,21,22 To investigate the mechanism of action of the Li81 antibody, we solved the crystal structure of the LINGO-1 ectodomain/Li81 Fab complex. 20 An unexpected feature of the structure was that the Li81 Fab contained two binding sites for LINGO-1, and this led to the formation of a heterotetrameric unit that contained 2 copies each of the Fab and LINGO-1, where the classical primary binding of the Fab through its complementarity-determining regions (CDRs) to LINGO-1 created a secondary binding site that recruited a second copy of LINGO-1 (Figure 1(b) vs. Figure 1 (a)).…”
Section: Introductionmentioning
confidence: 99%